CROSSROADS OF WAR: THE PEOPLE OF NKANDLA IN THE ZULU REBELLION OF 1906 - Thompson, Paul S. (Scientia Militaria - South African Journal of Military Studies, 2011)
The rebellion and NkandlaThe Zulu Rebellion of 1906 was the violent response to the imposition ofa poll tax of £1 on all adult males (with exempted categories) by the government ofthe British South African colony of Natal on the part of a section of the indigenous,Zulu-speaking people. The rebellion was in the nature of “secondary resistance” toEuropean colonization, and the poll tax was only the immediate cause of it. Not allthe African people (who made up 82% of the colony’s population) participated inthe rebellion; only a few did, but there was the potential for a mass uprising, whichinspired great fear among the European settlers (who made up just 8,3% of thepopulation) and prompted the colony’s responsible government to take quick andvigorous action to crush the rebellion before it could spread. The object of the rebels, beyond the removal of the poll tax, was to drive the white settlers out of thecountry and to restore the pre-colonial regime, although it was unclear just what theythought that might have been. In the case of most (but not all) of the those living inthe Province of Zululand, i.e. the northeastern quarter of the Colony of Natal, itmeant the restoration of the Zulu monarchy under the chief Dinuzulu.